2001
DOI: 10.1097/00007632-200104150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Structural Properties of the Lumbosacral Vertebral Endplates

Abstract: Highly significant regional strength and stiffness variations were identified in the lumbar and sacral endplates. The center of the bone, where implants are currently placed, is the weakest part of the lumbar endplates and is not the strongest region of the sacral endplate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
208
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(238 citation statements)
references
References 16 publications
25
208
2
3
Order By: Relevance
“…They also provided mechanical data proving that the anterior site of the endplate is weaker than the posterior site. Grant et al 16) demonstrated the mechanical weakness of the central region of the endplate using indentation tests. In addition, they showed that the superior endplate was mechanically weaker than the inferior endplate.…”
Section: Discussionmentioning
confidence: 99%
“…They also provided mechanical data proving that the anterior site of the endplate is weaker than the posterior site. Grant et al 16) demonstrated the mechanical weakness of the central region of the endplate using indentation tests. In addition, they showed that the superior endplate was mechanically weaker than the inferior endplate.…”
Section: Discussionmentioning
confidence: 99%
“…The initial advice for transforaminal lumbar interbody fusion (TLIF) was to place the intervertebral cage in the middle/posterior third of the disc space [25]. Posterolateral placement within the intervertebral space, where the endplate is thicker [8] and stronger [8,26], has been suggested following a biomechanical study assessing the risk of cage subsidence [14], whereas central placement has shown greater subsidence in a clinical study [15]. With regard to anterior placement, both a cadaveric [27] and a clinical study [28] involving TLIF found no difference in intervertebral lordosis when cages were placed in the anterior half of the disc space.…”
Section: Discussionmentioning
confidence: 99%
“…8,25 Lastfogel et al have speculated that a combination of forces on inferior screws may be one of the factors predisposing to failure of this device. 15 In mapping the structural properties of lumbosacral vertebral endplates, Grant et al 9 discovered that lateral margins were stronger than central areas, both anteriorly and posteriorly. Likewise, inferior lumbar endplates were significantly stronger and stiffer than their superior counterparts.…”
mentioning
confidence: 99%